2014
DOI: 10.1016/j.nicl.2014.01.012
|View full text |Cite
|
Sign up to set email alerts
|

Graph theoretical analysis indicates cognitive impairment in MS stems from neural disconnection

Abstract: BackgroundThe mechanisms underlying cognitive impairment in MS are still poorly understood. However, due to the specific pathology of MS, one can expect alterations in connectivity leading to physical and cognitive impairment.AimIn this study we aimed at assessing connectivity differences in EEG between cognitively impaired (CI) and cognitively preserved (CP) MS patients. We also investigated the influence of the measures used to construct networks.MethodsWe included 308 MS patients and divided them into two g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
27
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
7
1
1

Relationship

3
6

Authors

Journals

citations
Cited by 37 publications
(28 citation statements)
references
References 37 publications
1
27
0
Order By: Relevance
“…Moreover, we recently showed that cisplatin reduces arborization and spine density of pyramidal neurons in the cingulum [2]. Van Schependom et al described that neural disconnections, especially of white-matter tracts connecting both hemispheres seen in cognitively impaired versus cognitively preserved patients with multiple sclerosis, were responsible for the cognitive impairment observed in these patients [41]. Diffusion tensor neuroimaging of the brains of lung cancer patients indicates that cisplatin treatment results in an increased fractional anisotropy in areas of white matter in the cingulate cortex.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, we recently showed that cisplatin reduces arborization and spine density of pyramidal neurons in the cingulum [2]. Van Schependom et al described that neural disconnections, especially of white-matter tracts connecting both hemispheres seen in cognitively impaired versus cognitively preserved patients with multiple sclerosis, were responsible for the cognitive impairment observed in these patients [41]. Diffusion tensor neuroimaging of the brains of lung cancer patients indicates that cisplatin treatment results in an increased fractional anisotropy in areas of white matter in the cingulate cortex.…”
Section: Discussionmentioning
confidence: 99%
“…These studies have provided valuable information on the deviant organisation in the diseased brain, such as in Alzheimer's disease (Stam et al , 2007a, Dubovik et al , 2013, epilepsy (Bartolomei et al , 2006, Ibrahim et al , 2013, schizophrenia (Hinkley et al , 2010, Siebenhuhner et al , 2013, multiple sclerosis (Schoonheim et al , 2013, Van Schependom et al , 2014, Parkinson's disease (Fogelson et al , 2013), as well as in the healthy brain on topics as aging (Smit et al , 2012, Vecchio et al , 2014, gender differences (Boersma et al , 2011) and a healthy lifestyle (Douw et al , 2014). Furthermore, connectivity and functional brain network studies can be used in the clinical setting.…”
Section: Introduction and Rationalementioning
confidence: 99%
“…Cognitive impairment in MS may have different MRI correlates, including WM lesions, damage to the normal‐appearing WM and GM. The strong correlation of cognitive deterioration with cortical pathology does not exclude WM involvement to be predictive of deficits in single domains in the early stages, an observation in line with the hypothesis that an underlying disconnection syndrome due to the involvement of WM tracts might trigger cognitive symptoms . The heterogeneity in assessments, cognitive domains, and follow‐up periods may explain some of the discrepancies in the literature.…”
Section: Discussionmentioning
confidence: 87%